A Prenatal Presentation of CDK13-Related Disorder with a Novel Pathogenic Variant - Michael Gibbs; Alysa Poulin; Yanwei Xi; Bita Hashemi (Case Reports in Genetics)
Cyclin-dependent kinase 13 (CDK13) is a member of the cyclin-dependent serine/threonine protein kinase family. Members of this family are well known for their essential roles as master switches in cell cycle control. CDK13-related disorder is a newly described genetic condition with characteristic clinical features including mild to severe intellectual disability, developmental delay, neonatal hypotonia, a variety of facial dysmorphism, behavioral problems, congenital heart defects, and structural brain abnormalities. We report a case of prenatal diagnosis of CDK13-related disorder. Detection of cystic hygroma with thickened nuchal fold led to prenatal genetic investigation, which identified a novel de novo likely pathogenic variant in the CDK13 gene (c.900C > G, p.Tyr300∗). Pregnancy was terminated and autopsy was performed. To our best knowledge, this is the first reported case of prenatal presentation of this condition with a detailed phenotypic description of the affected fetus.